The Activity of the Bicameral Parliaments. Case Study: The United Kingdom of Great Britain and Northern Ireland - Mădălina Cocosatu (Acta Universitatis Danubius: Administratio, 2015)
Comparative research of various state legislative procedure presents a considerable theoretical and practical significance. It allows, on the one hand, the identification of legislation governing this legal institution and its analyzing and, for the other hand, the identification of the similarities and differences between these procedures. In this paper we analyze the activity of british parliament and the stages of the legislative procedure United Kingdom, country with bicameral parliaments. The study has considerable theoretical and practical significance, because by understanding the functioning of the legislative process, we can identify what is the role and how the bicameral parliaments contribute to the developing of policy making system. From the analysis that we do, we demonstrate that the structure, functioning and the roles of the two cameras are very different, House of Commons having broader powers regarding the legislative process to the House of Lords.